An evaluation of the dynamic qualities of isometric grip strength. Issue 11 (November 1988) - Helliwell, P S; Howe, A; Wright, V
Abstract : A strain gauged torsion dynamometer linked to a microprocessor was used to assess the dynamic qualities of isometric grip strength in patients with rheumatic diseases. Maximum grip strength, time to maximum grip, and percentage fatigue provide independent information on the grip. Time to maximum grip does not appear to be an objective correlate of subjective stiffness. The usefulness of these dynamic variables for the assessment of stiffness appears limited in arthritic disease, where pain may interfere with the maximum voluntary effort of the test.